Long-term outcomes of endovascular treatment of acute lower limb deep-vein thrombosis combined with May–Thurner syndrome: A single-center retrospective cohort study - Yunfeng Pang; Kailong Li; Xiaoqin Li; Yang Jin; Hao Cai; Fei Shao; Guodong Wang; Chong Ma; Gehua Wen; Ziqiang Sun; Song Jin (Vascular Investigation and Therapy, 2023)
OBJECTIVE: May–Thurner syndrome (MTS) is a common cause of lower-extremity deep venous thrombosis (DVT). Stenting is effective in the treatment of MTS; however, there are still complications that may affect the patency of the stent. In addition, the long-term efficacy of stenting remains uncertain. This retrospective study investigated the efficacy and prognosis of endovascular treatment of acute proximal DVT with MTS. MATERIALS AND METHODS: Between June 2014 and December 2017, 122 patients with acute symptomatic proximal DVT at our hospital underwent endovascular surgery. The clinical data of the patients were retrospectively collected including follow-up information. The analysis used the generalized additive mixed model and Kaplan–Meier curves (log-rank test). RESULTS: Of the 122 patients, 75 underwent only catheter-directed thrombolysis (CDT), and 47 underwent CDT with stent placement. Characteristics such as age (P = 0.630 ) and gender (P = 0.842) did not show significant differences between the two groups. The freedom from target lesion revascularization did not show significant differences between the two groups (P = 0.82). There were no significant differences between the two groups in the Venous Clinical Severity Score and Villalta Score. CONCLUSIONS: Endovascular treatment of acute lower limb DVT with MTS has good overall efficacy. In young patients with DVT caused by multiple factors besides MTS, prolonged anticoagulation and close follow-up may be more appropriate than primary stenting after thrombus clearance and significant relief of lower limb symptoms.